Insulated wire and method for manufacturing the same, coil, and electronic device
Through the inside of the inside of the insulating wire and heating the liquid crystal polyester to form an insulating layer, the problem of local discharge and insufficient deficitability of the insulating membrane under high voltage, and realize the extension and high deficiency of the voltage application.
Patent Information
- Application Number
- CN202310367664.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2022-04-19
- Filing Date
- 2023-04-07
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2043-04-07
AI Technical Summary
When using insulated wires in high voltage environments, local discharge of the insulating film causes deterioration of the insulating film, thereby shortening the voltage application life. At the same time, insulated wires need to be wound in a limited space, requiring high flexibility.
Liquid crystal polyester is used as the material of the insulating layer. A liquid composition of liquid crystal polyester and an aprotic solvent is coated on the outer peripheral side of the conductor and heated to form an insulating layer to ensure that the oxygen permeability of the insulating layer is 1×10- Below 15mol/m2.Pa.s.
The extension of the voltage applies and the high deflection of the insulating wire can be achieved, and it can maintain good insulation performance in a high -voltage environment while adapting to the needs of miniaturization and high output.
Smart Images

Figure CN116913580B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an insulated wire, and more particularly to an insulated wire having a long voltage application life, a manufacturing method thereof, a coil, and an electronic device. Background Art
[0002] In inverter-related devices (e.g., coils for electronic devices such as high-speed switching elements, inverter motors, and transformers), insulated wires (e.g., enameled wires) having an insulating resin coating (insulating film) formed around the conductor are used as magnetic conductors.
[0003] In recent years, with the popularity of hybrid vehicles and electric vehicles, it is necessary to improve motor efficiency and operate motors and control converters at high voltages. When using insulated wires at such high voltages, partial discharge (corona discharge) occurs on the surface of the insulating film, causing degradation of the insulating film. In order to suppress this partial discharge, a resin with a low dielectric constant is used as a constituent material of the insulating film.
[0004] As described above, insulated wires need to have high insulation resistance in high voltage environments to extend their voltage application life. In addition, the demand for miniaturization and high output of rotary motors such as automobile motors is increasing, and it is necessary to wind the insulated wire on a small-sized bobbin, increase the winding density of the insulated wire, or put as many bent insulated wires as possible into a limited space such as a stator slot (status lot). Therefore, such insulated wires are required to have not only high insulation resistance but also high flexibility. Summary of the invention
[0005] In view of the above, an object of the present invention is to provide an insulated wire having a long voltage application life and excellent flexibility, a method for producing the insulated wire, and a coil and an electronic device using the insulated wire.
[0006] The present invention provides an insulated wire, comprising: a conductor, and an insulating layer laminated on the outer peripheral side of the conductor. The insulating layer comprises liquid crystal polyester, and the oxygen permeability of the insulating layer is 1×10 -15 mol / m 2 .Pa.s below.
[0007] In one embodiment of the present invention, the liquid crystal polyester comprises structural units from the following (A), (B), and (C),
[0008] (A) Aromatic hydroxycarboxylic acid
[0009] (B) Aromatic dicarboxylic acid
[0010] (C) at least one compound selected from the group consisting of aromatic diols, aromatic diamines, and aromatic amines having a phenolic hydroxyl group.
[0011] In one embodiment of the present invention, the liquid crystal polyester comprises structural units from the following (A'), (B'), and (C'),
[0012] (A')-O-Ar 1 -CO-
[0013] (B')-CO-Ar 2 -CO-
[0014] (C')-X-Ar 3 -Y-
[0015] Among them, Ar 1 represents phenylene, naphthylene or biphenylene, Ar 2 represents a phenylene group, a naphthylene group, a biphenylene group, or a group formed by condensation of multiple aromatic groups, Ar 3 represents a phenylene group or a group formed by condensation of a plurality of aromatic groups, and X and Y represent -O- or -NH-, respectively.
[0016] In one embodiment of the present invention, the liquid crystal polyester comprises structural units from the following (A'), (B'), and (C"),
[0017] (A')-O-Ar 1 -CO-
[0018] (B')-CO-Ar 2 -CO-
[0019] (C”)-NH-Ar 3 -Y-
[0020] Among them, Ar 1 represents phenylene, naphthylene or biphenylene, Ar 2 represents a phenylene group, a naphthylene group, a biphenylene group, or a group formed by condensation of multiple aromatic groups, Ar 3 represents a phenylene group or a group formed by condensation of a plurality of aromatic groups, and Y represents -O- or -NH-.
[0021] In one embodiment of the present invention, the monomers constituting the above-mentioned (C") include aromatic hydroxylamine and aromatic hydroxyamide.
[0022] In one embodiment of the present invention, based on 100 mol% of the total amount of monomers constituting the above-mentioned (C"), the amount of aromatic hydroxylamine used is 30-90 mol%, and the amount of aromatic hydroxyamide used is 10-70 mol%.
[0023] In one embodiment of the present invention, the oxygen permeability of the insulating layer is 8×10 -16 mol / m 2 .Pa.s below.
[0024] In one embodiment of the present invention, the oxygen permeability of the insulating layer is 5×10 -16 mol / m 2 .Pa.s below.
[0025] In one embodiment of the present invention, the thickness of the insulating layer is greater than or equal to 2 μm and less than or equal to 50 μm.
[0026] The present invention further provides a method for manufacturing an insulated wire, wherein the method comprises the following steps:
[0027] A coating step of coating a liquid composition including a liquid crystal polyester and an aprotic solvent on the outer peripheral side of the conductor, and
[0028] In the heating step, the conductor coated with the liquid composition is heated.
[0029] The present invention further provides a coil, comprising the above-mentioned insulated wire.
[0030] The present invention further provides an electronic device, comprising the coil as described above.
[0031] As described above, since the insulating layer in the insulated wire of the present invention has a specific oxygen permeability, an insulated wire having a long voltage application life and excellent flexibility can be obtained. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 It is a cross-sectional view of an insulated wire according to one embodiment of the present invention.
[0033] Description of Reference Numerals
[0034] 1: Insulated wire
[0035] 11: Conductor
[0036] 12: Insulation layer
[0037] 13: Chamfer DETAILED DESCRIPTION
[0038] [Insulated wire]
[0039] Figure 1 FIG. 1 is a cross-sectional view of an insulated wire according to an embodiment of the present invention. Figure 1 As shown in FIG. 1 , the insulated wire 1 of the present invention includes: a conductor 11 and an insulating layer 12 laminated on the outer peripheral side of the conductor 11. The insulating layer 12 includes liquid crystal polyester, and the oxygen permeability of the insulating layer 12 is 1×10-15 mol / m 2 .Pa.s or less. Hereinafter, each member of the insulated wire will be described in detail.
[0040] [conductor]
[0041] As the conductor in the insulated wire, any conductor conventionally used for insulated wires can be used without particular limitation, and examples thereof include metal conductors such as copper wires and aluminum wires.
[0042] As a preferred example of the conductor in the insulated wire of the present invention, Figure 1 As shown, the conductor 11 having a rectangular cross section (flat shape) is used, but a conductor having a square, circular or elliptical cross section may also be used.
[0043] In flat conductors, such as Figure 1 As shown, from the viewpoint of suppressing partial discharge at the corners, it is preferable that the flat conductor 11 has chamfers 13 at four corners. The curvature radius of the chamfer 13 is preferably 0.6 mm or less, and more preferably 0.2 mm to 0.4 mm.
[0044] The size of the conductor is not particularly limited. If it is a flat conductor, the width (long side) of its rectangular cross section is preferably 1.0 mm to 5.0 mm, more preferably 1.4 mm to 4.0 mm; the thickness (short side) is preferably 0.4 mm to 3.0 mm, more preferably 0.5 mm to 2.5 mm. The ratio of thickness to width (short side: long side) is preferably 1:1 to 1:4. If it is a conductor with a circular cross section, the cross-sectional diameter is preferably 0.3 mm to 3.0 mm, more preferably 0.4 mm to 2.7 mm.
[0045] [Insulation layer]
[0046] As an insulating layer in insulated wires, it can be used as Figure 1 As shown, only a single-layer insulating layer 12 is stacked on the conductor 11, and the insulating layer 12 can also be multi-layer. The thickness of the insulating layer is 2μm to 50μm, preferably 10μm to 50μm, and more preferably 20μm to 40μm. When the insulating layer is a multi-layer structure, the thickness of the insulating layer is calculated based on the total thickness of the multi-layer insulating layers. When the thickness of the insulating layer is less than 2μm, sufficient strength cannot be obtained; and when the thickness of the insulating layer is greater than 50μm, sufficient flexibility cannot be obtained, and thus it is not good.
[0047] [Oxygen permeability of insulating layer]
[0048] As the insulating layer in the insulated wire, its oxygen permeability is 1×10 -15 mol / m 2 .Pa.s or less, preferably 8×10 -16 mol / m2 .Pa.s or less, more preferably 5×10 -16 mol / m 2 If the oxygen permeability of the insulating layer is not within the above range, the voltage application life of the obtained insulated wire is poor.
[0049] [Liquid crystal polyester]
[0050] The liquid crystal polyester is used as an insulating layer in an insulated wire. The liquid crystal polyester in the present invention is a polyester called a thermotropic liquid crystal polymer, which is a melt showing optical anisotropy at a temperature of 450°C or less.
[0051] The liquid crystal polyester in the present invention comprises structural units derived from the following (A), (B), and (C):
[0052] (A) Aromatic hydroxycarboxylic acid
[0053] (B) Aromatic dicarboxylic acid
[0054] (C) at least one compound selected from the group consisting of aromatic diols, aromatic diamines, and aromatic amines having a phenolic hydroxyl group.
[0055] More specifically, the liquid crystal polyester in the present invention preferably includes structural units derived from the following (A'), (B'), and (C'),
[0056] (A')-O-Ar 1 -CO-
[0057] (B')-CO-Ar 2 -CO-
[0058] (C')-X-Ar 3 -Y-
[0059] Among them, Ar 1 represents phenylene, naphthylene or biphenylene, Ar 2 represents a phenylene group, a naphthylene group, a biphenylene group, or a group formed by condensation of multiple aromatic groups, Ar 3 represents a phenylene group or a group formed by condensation of a plurality of aromatic groups, and X and Y represent -O- or -NH-, respectively.
[0060] More specifically, the liquid crystal polyester in the present invention preferably includes structural units derived from the following (A'), (B'), and (C"),
[0061] The content of the structural unit derived from (C") is 10 to 35 mol% relative to all structural units.
[0062] (A')-O-Ar 1 -CO-
[0063] (B')-CO-Ar 2 -CO-
[0064] (C”)-NH-Ar 3 -Y-
[0065] Among them, Ar 1 represents phenylene, naphthylene or biphenylene, Ar 2 represents a phenylene group, a naphthylene group, a biphenylene group, or a group formed by condensation of multiple aromatic groups, Ar 3 represents a phenylene group or a group formed by condensation of a plurality of aromatic groups, and Y represents -O- or -NH-.
[0066] It should be noted here that the above-mentioned “structural unit derived from (A')” corresponds to the above-mentioned “structural unit derived from (A)”. The above-mentioned “structural unit derived from (B')” corresponds to the above-mentioned “structural unit derived from (B)”. The above-mentioned “structural unit derived from (C')” and “structural unit derived from (C")” correspond to the above-mentioned “structural unit derived from (C)”. The structural units included in the liquid crystal polyester are described in detail below.
[0067] (A) Aromatic hydroxycarboxylic acid
[0068] The structural unit derived from the (A) aromatic hydroxycarboxylic acid includes structural units represented by the following formulae (A-1) to (A-5), wherein the aromatic ring may be substituted with a halogen atom, an alkyl group or an aromatic group.
[0069]
[0070]
[0071] Among them, the alkyl group as a substituent in the aromatic ring is usually an alkyl group having 1 to 10 carbon atoms, preferably methyl, ethyl, n-propyl, or n-butyl. The aromatic group as a substituent in the aromatic ring is usually an aromatic group having 6 to 20 carbon atoms, preferably phenyl.
[0072] Specific examples of the (A) aromatic hydroxycarboxylic acid include p-hydroxybenzoic acid, m-hydroxybenzoic acid, 6-hydroxy-2-naphthoic acid, 3-hydroxy-2-naphthoic acid, 4-hydroxy-1-naphthoic acid, and 4-(4-hydroxyphenyl)benzoic acid.
[0073] (B) Aromatic dicarboxylic acid
[0074] The structural unit derived from (B) aromatic dicarboxylic acid can be exemplified by the structural units represented by the following formulae (B-1) to (B-10), wherein the aromatic ring can be substituted by a halogen atom, an alkyl group or an aromatic group. The specific substituents are the same as those listed for the above-mentioned (A) aromatic hydroxycarboxylic acid, and will not be described in detail here.
[0075]
[0076]
[0077] Specific examples of the (B) aromatic dicarboxylic acid include terephthalic acid, isophthalic acid, 2,6-naphthalene dicarboxylic acid, 1,5-naphthalene dicarboxylic acid, biphenyl-4,4'-dicarboxylic acid, diphenyl ether-4,4'-dicarboxylic acid, diphenyl sulfide-4,4'-dicarboxylic acid, diphenyl sulfone-4,4'-dicarboxylic acid, and benzophenone-4,4'-dicarboxylic acid.
[0078] (C) at least one compound selected from aromatic diols, aromatic diamines, and aromatic amines having a phenolic hydroxyl group
[0079] Aromatic diols
[0080] The structural units derived from the aromatic diols include the structural units shown in the following formulas (C-1-1) to (C-1-10), wherein the aromatic rings may be substituted by halogen atoms, alkyl groups or aromatic groups. The specific substituents are the same as those listed for the aromatic hydroxycarboxylic acids (A) above, and will not be described in detail here.
[0081]
[0082]
[0083] Specific examples of the aromatic diol include hydroquinone, resorcinol, 2,6-naphthalene diol, 1,5-naphthalene diol, biphenyl-4,4'-diol, biphenyl-2,5-diol, 2,2-bis(4-hydroxyphenyl)propane, 2,2-bis(4-hydroxy-3,5-dimethylphenyl)propane, bis(4-hydroxyphenyl)ether, bis-(4-hydroxyphenyl)ketone, and bis-(4-hydroxyphenyl)sulfone.
[0084] Aromatic diamines
[0085] The structural unit derived from the aromatic diamine can be exemplified by the structural units shown in the following formulas (C-2-1) to (C-2-10), wherein the aromatic ring may be substituted by a halogen atom, an alkyl group or an aromatic group. The specific substituents are the same as those listed for the aromatic hydroxycarboxylic acid (A) above, and will not be described in detail here.
[0086]
[0087]
[0088]
[0089] Specific examples of the aromatic diamine include p-phenylenediamine, m-phenylenediamine, biphenyl-4,4′-diamine, bis(4-aminophenyl)methane, bis(4-aminophenyl)ether, bis-(4-aminophenyl)ketone, and bis-(4-aminophenyl)sulfone.
[0090] Aromatic amines with phenolic hydroxyl groups
[0091] Examples of the structural unit derived from an aromatic amine having a phenolic hydroxyl group include structural units represented by the following formulae (C-3-1) to (C-3-6), wherein the aromatic ring may be substituted with a halogen atom, an alkyl group or an aromatic group.
[0092] The specific substituents are the same as those listed for the above (A) aromatic hydroxycarboxylic acid, which will not be described in detail here.
[0093]
[0094] Specific examples of aromatic amines having phenolic hydroxyl groups include aromatic hydroxylamines and aromatic hydroxyamides. Examples of aromatic hydroxylamines include 3-aminophenol, 4-aminophenol, 4-amino-4'-hydroxybiphenyl, and the like. Examples of aromatic hydroxyamides include 3-hydroxyacetanilide, 4-hydroxyacetanilide, and the like. If the monomers constituting (C") include aromatic hydroxylamines and aromatic hydroxyamides, the voltage application life of the resulting insulated wire is better.
[0095] Furthermore, as the structural units constituting the above-mentioned (A), (B), and (C), not only the above-mentioned monomers but also ester derivatives or amide derivatives of the above-mentioned monomers can be used.
[0096] Among them, examples of the ester derivatives or amide derivatives of carboxylic acids include: highly reactive derivatives such as acid chloride compounds or acid anhydride compounds generated by subjecting a carboxylic acid group to a polyester formation reaction or a polyamide formation reaction; and ester or amide derivatives formed by reacting a carboxylic acid group with alcohols, glycols or amines of a polyester or polyamide generated by an ester exchange reaction or an amide exchange reaction.
[0097] Examples of the ester derivative of a phenolic hydroxyl group include a derivative obtained by reacting a phenolic hydroxyl group with a carboxylic acid group through an ester exchange reaction to form a polyester, thereby forming an ester derivative.
[0098] Examples of the amide derivative of an amino group include an amide derivative obtained by reacting an amino group with a carboxylic acid group through an amide exchange reaction to form a polyamide.
[0099] [Content of Each Structural Unit of Liquid Crystalline Polyester]
[0100] The lower limit of the content of the structural unit derived from (A) is preferably 10 mol % relative to all the structural units. The upper limit of the content of the structural unit derived from (A) is preferably 70 mol %, more preferably 60 mol %, and further preferably 50 mol % relative to all the structural units.
[0101] The lower limit of the content of the structural unit derived from (B) is preferably 15 mol %, more preferably 20 mol %, and further preferably 25 mol %, relative to all structural units. The upper limit of the content of the structural unit derived from (B) is preferably 45 mol %, relative to all structural units.
[0102] The lower limit of the content of the structural unit derived from (C) is preferably 15 mol %, more preferably 20 mol %, and further preferably 25 mol %, relative to all structural units. The upper limit of the content of the structural unit derived from (C) is preferably 45 mol %, relative to all structural units.
[0103] The lower limit of the content ratio of the structural unit derived from (B) to the structural unit derived from (C) (B / C) is preferably 0.9, more preferably 1, and further preferably 1.2, and the upper limit is preferably 2, more preferably 1.5, and further preferably 1.3.
[0104] In addition, in the liquid crystal polyester, the structural units from (A), (B), and (C) may contain only one type, or contain two or more types. In addition, the liquid crystal polyester may also contain other structural units other than (A), (B), and (C). The content of other structural units is preferably 10 mol% or less, more preferably 5 mol% or less, relative to all structural units.
[0105] Among them, when the monomers constituting the structural unit derived from (C") include aromatic hydroxylamine and aromatic hydroxyamide, the voltage application life of the obtained insulated wire is better.
[0106] Based on the total amount of monomers constituting the structural unit derived from (C") being 100 mol%, the amount of aromatic hydroxylamine used is preferably 30 to 90 mol%, and the amount of aromatic hydroxyamide used is preferably 10 to 70 mol%. When the amounts of aromatic hydroxylamine and aromatic hydroxyamide used fall within the above ranges, the voltage application life of the obtained insulated wire is better.
[0107] The liquid crystal polyester of the present invention has a weight average molecular weight of 10,000 to 100,000, preferably 13,000 to 95,000, and more preferably 15,000 to 90,000, as measured by gel permeation chromatography (GPC) and in terms of polystyrene.
[0108] [Method for producing liquid crystal polyester]
[0109] The method for producing the liquid crystal polyester of the present invention is not particularly limited, and examples thereof include: acylation of (A) an aromatic hydroxycarboxylic acid and (C) a compound selected from at least one of an aromatic diol, an aromatic diamine, and an aromatic amine having a phenolic hydroxyl group with an excess of fatty acid anhydride to obtain an acylate, and then polymerizing the acylate with (A) an aromatic hydroxycarboxylic acid and / or (B) an aromatic dicarboxylic acid through an ester exchange / amide exchange reaction to obtain the acylate.
[0110] In the acylation reaction, the amount of fatty acid anhydride added is preferably 1.0 to 1.2 equivalents, more preferably 1.05 to 1.1 equivalents, relative to the total amount of phenolic hydroxyl groups and amine groups. If the amount of fatty acid anhydride added is too small, there is a tendency for the reaction apparatus to be clogged due to the sublimation of the acylate or other reactants during polymerization reactions such as transesterification or transamide exchange; if the amount of fatty acid anhydride added is too large, there is a problem that the obtained liquid crystal polyester is easily colored.
[0111] The reaction conditions for the acylation reaction are preferably 130° C. to 180° C. for 5 minutes to 10 hours, and more preferably 140° C. to 160° C. for 10 minutes to 3 hours.
[0112] In the acylation reaction, as fatty acid anhydride, there is no particular limitation, and examples thereof include acetic anhydride, propionic anhydride, butyric anhydride, isobutyric anhydride, valeric anhydride, pivalic anhydride, 2-ethylhexanoic anhydride, dichloroacetic anhydride, trichloroacetic anhydride, monobromoacetic anhydride, dibromoacetic anhydride, tribromoacetic anhydride, monofluoroacetic anhydride, difluoroacetic anhydride, trifluoroacetic anhydride, glutaric anhydride, maleic anhydride, succinic anhydride, β-bromopropionic anhydride, etc. Fatty acid anhydride can be used only one or two or more. From the viewpoint of price and operability, acetic anhydride, propionic anhydride, butyric anhydride or isobutyric anhydride are preferred, and acetic anhydride is more preferred.
[0113] In the transesterification / amidation reaction, the acyl content of the acylated product is preferably 0.8 to 1.2 equivalents relative to the carboxyl content. The reaction temperature of the transesterification / amidation reaction is preferably 400°C or less, more preferably 350°C or less. In addition, the heating rate of the reaction is preferably 0.1 to 50°C / min, more preferably 0.3 to 5°C / min. In addition, in order to shift the equilibrium between the reactants and the products, it is preferred that the by-product fatty acid or the unreacted fatty acid anhydride be distilled from the reaction system by evaporation or the like during the reaction.
[0114] In addition, the acylation reaction and the transesterification / transamidation reaction can be carried out in the presence of a catalyst. As the catalyst, substances known as catalysts for polyester polymerization can be used, such as metal salts such as magnesium acetate, stannous acetate, tetrabutyl titanate, lead acetate, sodium acetate, potassium acetate, antimony trioxide, and organic compounds such as N,N-dimethylaminopyridine and N-methylimidazole. The catalyst is usually present during the acylation reaction, and it is not necessary to remove the catalyst even after the acylation reaction. If the catalyst is not removed, the next step of treatment can be directly carried out. In addition, the above catalyst can be further added when the next treatment is carried out.
[0115] The polymerization reaction of the transesterification / amidation reaction is usually carried out by melt polymerization, but melt polymerization and solid phase polymerization can also be used in combination. Solid phase polymerization can be carried out by a known solid phase polymerization method after extracting the polymer from the melt polymerization process, solidifying it, and crushing it into powder or flakes. Specifically, it can be listed as a method of heat treatment in a solid phase state at 20°C to 350°C under a nitrogen environment for 1 hour to 30 hours. Solid phase polymerization can be carried out under stirring or in a static state without stirring. In addition, as long as an appropriate stirring mechanism is provided, the melt polymerization tank and the solid phase polymerization tank can be the same reaction tank. After solid phase polymerization, the obtained liquid crystal polyester can be granulated by a known method.
[0116] The liquid crystal polyester of the present invention includes at least one obtained by the following method, and specific examples of the method include adding monomers in batches during the acylation reaction, changing the reaction temperature during the acylation reaction, or changing the reaction temperature during the ester exchange / amide exchange reaction in stages.
[0117] [Manufacturing method of insulated electric wire]
[0118] As a method for producing an insulated wire, the following steps can be mentioned:
[0119] (1) a coating step of coating a liquid composition including a liquid crystal polyester and an aprotic solvent on the outer peripheral side of the conductor, and
[0120] (2) A heating step of heating the conductor coated with the liquid composition.
[0121] Hereinafter, each step will be described in detail.
[0122] (1) Coating process
[0123] In the coating step, the liquid composition comprising the liquid crystal polyester of the present invention and the aprotic solvent is applied directly or via another layer to the outer circumference of the conductor. Here, before the coating step, another primer layer may be formed on the surface of the conductor by a known method.
[0124] Preferred aprotic solvents include: halogen solvents such as 1-chlorobutane, chlorobenzene, 1,1-dichloroethane, 1,2-dichloroethane, chloroform, and 1,1,2,2-tetrachloroethane; ether solvents such as diethyl ether, tetrahydrofuran, and 1,4-dioxane; ketone solvents such as acetone and cyclohexanone; ester solvents such as ethyl acetate; lactone solvents such as γ-butyrolactone; carbonate solvents such as ethylene carbonate and propylene carbonate; amine solvents such as triethylamine and pyridine; nitrile solvents such as acetonitrile and succinonitrile; amide solvents such as N,N'-dimethylformamide, N,N'-dimethylacetamide, tetramethylurea, and N-methyl-2-pyrrolidone; nitro solvents such as nitromethane and nitrobenzene; sulfide solvents such as dimethyl sulfoxide and sulfolane; and phosphoric acid solvents such as hexamethylphosphoric acid amide and tri-n-butyl phosphate.
[0125] These solvents can be used alone or in combination of two or more. Among them, from the viewpoint of environmental impact, it is preferred to use a solvent that does not contain halogen atoms, and from the viewpoint of solubility, it is preferred to use a solvent with a dipole moment of 3 or more and 5 or less. Specifically, it is preferred to use amide solvents such as N,N'-dimethylformamide, N,N'-dimethylacetamide, tetramethylurea, N-methyl-2-pyrrolidone; lactone solvents such as γ-butyrolactone. It is more preferred to use solvents such as N,N'-dimethylformamide, N,N'-dimethylacetamide, N-methyl-2-pyrrolidone.
[0126] The concentration of the liquid crystal polyester in the liquid composition can be appropriately selected according to the application, preferably 0.5% to 50% by mass, and more preferably 5% to 30% by mass. When the concentration of the liquid crystal polyester is less than 0.5% by mass, it may be difficult to apply uniformly due to the low viscosity of the solution, and more heat needs to be supplied to dry the solvent, resulting in increased costs; and when the concentration of the liquid crystal polyester exceeds 50% by mass, it may be difficult to apply uniformly due to the high viscosity of the solution, and the liquid composition itself is also easily colloidized, which is not good.
[0127] Furthermore, a liquid composition obtained by dissolving a liquid crystal polyester in a solvent may be used as a coating liquid as it is, but it is preferably passed through a filter or the like to remove fine foreign matter contained in the solution.
[0128] Furthermore, the liquid composition may contain components such as other resins, other solvents, other fillers or additives in addition to the above-mentioned liquid crystal polyester and aprotic solvent.
[0129] As a method for applying the liquid composition to the outer circumference of the conductor, for example, there can be mentioned a method using a coating device having a liquid composition tank for storing the liquid composition and a coating die. According to the coating device, when the conductor is inserted into the liquid composition tank, the liquid composition adheres to the outer circumference of the conductor and then passes through the coating die, so that the liquid composition has a substantially uniform thickness.
[0130] (2) Heating process
[0131] In the heating step, the liquid composition applied on the conductor or the linear body of the primer layer formed in the coating step is heated to form an insulating layer. The solvent in the liquid composition is volatilized by the heating to form an insulating layer with excellent electrical, mechanical and thermal properties.
[0132] The apparatus used in the heating step is not particularly limited, and examples thereof include a cylindrical baking oven that is long in the running direction of the conductor. The heating method is not particularly limited, and examples thereof include conventionally known methods such as hot air heating, infrared heating, and high-frequency heating.
[0133] As the heating conditions of the heating process, it is preferred to heat at 300°C or more for 10 seconds or more and less than 3 hours, more preferably to heat at 300°C or more for 10 seconds or more and less than 15 minutes, and further preferably to heat at 300°C or more for 10 seconds or more and less than 30 seconds. By heating at high temperature for a short time, the thermal conductivity in the thickness direction of the insulating layer can be further improved. If the heating time is less than 10 seconds, the evaporation of the solvent and the formation of the insulating layer are insufficient, and the appearance, electrical properties, mechanical properties and thermal properties of the insulated wire may deteriorate. In principle, even if the heating time is shortened by increasing the heating temperature to a higher temperature, the amount of heat given to the insulating layer can be equalized, but excessive rapid heating will cause blistering and degradation of mechanical properties of the insulating layer. The upper limit of the heating temperature is not particularly limited, but due to the deterioration of the characteristics of the insulated wire, productivity, cost, etc., the upper limit is, for example, 400°C. On the other hand, if the heating time exceeds 3 hours, not only the thermal conductivity in the thickness direction of the insulating layer is reduced, but also the characteristics of the insulated wire are reduced, which is not good in terms of productivity, cost, etc.
[0134] In addition, the insulated wire formed by the heating process may be further heated as needed. By further heating, the electrical, mechanical and thermal properties of the insulated wire may be improved. The heating device is not particularly limited, and for example, batch heating may be performed after the insulated wire is manufactured using the above-mentioned heating device. The heating method is not particularly limited, and may be performed by conventionally known methods such as hot air heating, infrared heating, and high-frequency heating.
[0135] The coating process and heating process are usually repeated several times. By repeating the coating process and heating process, the thickness of the insulating layer can be increased. At this time, the aperture of the coating mold should be appropriately adjusted according to the number of repetitions.
[0136] [Coil and electronic equipment]
[0137] The insulated wire of the present invention can be used as a coil in various electronic devices and other fields that require electrical properties (voltage resistance). For example, the insulated wire of the present invention can be used in motors, transformers, etc. to form high-performance electronic devices. It is particularly suitable for use as a winding of a drive motor of a hybrid vehicle (HV) or an electric vehicle (EV). As described above, according to the present invention, an electronic device such as a HV and EV drive motor using the insulated wire of the present invention as a coil can be provided.
[0138] The coil of the present invention may have a shape suitable for various electronic devices, for example, a coil shape obtained by winding the insulated wire of the present invention, or a shape obtained by bending the insulated wire of the present invention and then electrically connecting specific portions.
[0139] The coil formed by winding the insulated wire of the present invention is not particularly limited, and for example, a coil formed by winding a long insulated wire into a spiral shape can be cited. In such a coil, the number of windings of the insulated wire is not particularly limited. Usually, an iron core or the like is used when winding the insulated wire.
[0140] [Example]
[0141] [Synthesis Example of Liquid Crystal Polyester]
[0142] Synthesis example 1
[0143] In the reaction vessel provided with nitrogen inlet, agitator, heater, condensing tube and thermometer, after importing nitrogen, add 138.1g (1.0mol) of p-hydroxybenzoic acid (hereinafter referred to as a1), 747.6g (4.5mol) of terephthalic acid (hereinafter referred to as b1), 453.5g (3.0mol) of 3-hydroxyacetanilide (hereinafter referred to as c2-1) and 816.7g (8.0mol) of diacetyl anhydride. Then, under nitrogen gas stream, slowly stir the above-mentioned components and make the solution warm up to 150 ℃, and at this temperature, add 3-aminophenol (hereinafter referred to as c1-1) of total amount 163.7g (1.5mol) three times (each time at intervals of 1 hour), remain at the above-mentioned temperature and react for 1 hour afterwards. Then, the acetic acid of by-product and unreacted diacetyl anhydride are distilled off from the reaction system, and after the solution is warmed up to 300 ℃ with a heating rate of 1.0 ℃ / minute, decompression treatment is carried out at 300 ℃ temperature. After reacting at 300°C for 1 hour, the product was taken out of the reaction vessel and cooled to room temperature. The cooled product was crushed with a pulverizer to obtain a powdered liquid crystal polyester (A-1) of Synthesis Example 1. 8 g of the powdered liquid crystal polyester (A-1) was added to 92 g of N-methyl-2-pyrrolidone and heated to 140°C to completely dissolve it, thereby obtaining a brown transparent solution.
[0144] Synthesis example 2
[0145] In the reaction vessel that is provided with nitrogen inlet, agitator, heater, condensing tube and thermometer, after importing nitrogen, add the m-hydroxybenzoic acid (hereinafter referred to as a2) of 276.2g (2.0mol), the isophthalic acid (hereinafter referred to as b2) of 664.6g (4.0mol), the 4-hydroxyacetanilide (hereinafter referred to as c2-2) of 302.3g (2.0mol) and the diacetic anhydride of 918.8g (9.0mol). Then, under nitrogen gas stream, slowly stir above-mentioned composition and make solution be warming up to 150 ℃, and at this temperature, add the 4-aminophenol (hereinafter referred to as c1-2) of total amount 218.3g (2.0mol) three times (each time at intervals of 1 hour), remain at the above-mentioned temperature and react 1 hour afterwards. Then, the acetic acid of by product and unreacted diacetic anhydride are distilled off from reaction system, and after making solution be warming up to 300 ℃ with the heating rate of 1.0 ℃ / minute, carry out decompression treatment at 300 ℃ temperature. After reacting at 300°C for 1 hour, the product was taken out of the reaction vessel and cooled to room temperature. The cooled product was crushed with a pulverizer to obtain a powdered liquid crystal polyester (A-2) of Synthesis Example 2. 8 g of the powdered liquid crystal polyester (A-2) was added to 92 g of N-methyl-2-pyrrolidone and heated to 140°C to completely dissolve it to obtain a brown transparent solution.
[0146] Synthesis example 3
[0147] After nitrogen was introduced into a reaction vessel equipped with a nitrogen inlet, a stirrer, a heater, a condenser and a thermometer, 564.5 g (3.0 mol) of 6-hydroxy-2-naphthoic acid (hereinafter referred to as a3), 756.7 g (3.5 mol) of 2,6-naphthalenedicarboxylic acid (hereinafter referred to as b3) and 1123.0 g (11.0 mol) of acetic anhydride were added. Then, the above components were slowly stirred under a nitrogen stream to raise the temperature of the solution to 150°C, and a total of 648.3 g (3.5 mol) of 4-amino-4'-hydroxybiphenyl (hereinafter referred to as c1-3) was added three times (each time with an interval of 1 hour) at this temperature, and then the reaction was maintained at the above temperature for 1 hour. Then, the by-product acetic acid and unreacted acetic anhydride were distilled off from the reaction system, and the solution was heated to 300°C at a heating rate of 1.0°C / min, and then decompression treatment was performed at a temperature of 300°C. After reacting at 300°C for 1 hour, the product was taken out of the reaction vessel and cooled to room temperature. The cooled product was crushed with a pulverizer to obtain a powdered liquid crystal polyester (A-3) of Synthesis Example 3. 8 g of the powdered liquid crystal polyester (A-3) was added to 92 g of N-methyl-2-pyrrolidone and heated to 140°C to completely dissolve it to obtain a brown transparent solution.
[0148] Synthesis example 4
[0149] After nitrogen was introduced into a reaction vessel equipped with a nitrogen inlet, a stirrer, a heater, a condenser and a thermometer, 552.5 g (4.0 mol) of a1, 774.7 g (3.0 mol) of diphenyl ether-4,4'-dicarboxylic acid (hereinafter referred to as b4) and 816.7 g (8.0 mol) of acetic anhydride were added. Then, the above components were slowly stirred under a nitrogen stream to heat the solution to 150°C, and a total of 453.5 g (3.0 mol) of c2-1 was added three times (each time with an interval of 1 hour) at this temperature, and then the reaction was maintained at the above temperature for 1 hour. Then, the by-product acetic acid and unreacted acetic anhydride were distilled off from the reaction system, and the solution was heated to 300°C at a heating rate of 1.0°C / min, and then decompression treatment was performed at a temperature of 300°C. After reacting at a temperature of 300°C for 1 hour, the product was taken out of the reaction vessel and cooled to room temperature. The cooled product was crushed with a crusher to obtain a powdered liquid crystal polyester (A-4) of Synthesis Example 4. 8 g of the powdered liquid crystal polyester (A-4) was added to 92 g of N-methyl-2-pyrrolidone and heated to 140° C. to completely dissolve it, thereby obtaining a brown transparent solution.
[0150] Synthesis example 5
[0151] After nitrogen was introduced into a reaction vessel equipped with a nitrogen inlet, a stirrer, a heater, a condenser and a thermometer, 690.6 g (5.0 mol) of a2, 675.6 g (2.5 mol) of benzophenone-4,4'-dicarboxylic acid (hereinafter referred to as b5), 277.8 g (1.5 mol) of c1-3, 151.2 g (1.0 mol) of c2-2 and 1020.9 g (10.0 mol) of acetic anhydride were added. Then, the above components were slowly stirred under a nitrogen flow to raise the temperature of the solution to 140°C, react at this temperature for 1 hour, then raised to 150°C and reacted for 1 hour, and finally raised to 160°C and reacted for 1 hour. Then, the by-product acetic acid and unreacted acetic anhydride were distilled off from the reaction system, and the solution was raised to 300°C at a heating rate of 1.0°C / min, and then decompressed at 300°C. After reacting at 300°C for 1 hour, the product was taken out of the reaction vessel and cooled to room temperature. The cooled product was crushed with a pulverizer to obtain a powdered liquid crystal polyester (A-5) of Synthesis Example 5. 8 g of the powdered liquid crystal polyester (A-5) was added to 92 g of N-methyl-2-pyrrolidone and heated to 140°C to completely dissolve it, thereby obtaining a brown transparent solution.
[0152] Synthesis Example 6 to Synthesis Example 8
[0153] The synthesis methods of the liquid crystal polyesters of Synthesis Examples 6 to 8 are the same as that of Synthesis Example 5. The difference is that the amount of each monomer and acetic anhydride used is changed. The formulas are shown in Tables 1 and 2.
[0154] Synthesis example 9
[0155] In a reaction vessel equipped with a nitrogen inlet, a stirrer, a heater, a condenser and a thermometer, nitrogen was introduced, and then 376.36 g (2.0 mol) of a3, 1032.9 g (4.0 mol) of b4, 222.3 g (1.2 mol) of c1-3, 423.2 g (2.8 mol) of c2-1 and 816.7 g (8.0 mol) of acetic anhydride were added. Then, the above components were slowly stirred under a nitrogen stream to heat the solution to 140°C, and reacted at this temperature for 3 hours. Then, the by-product acetic acid and unreacted acetic anhydride were distilled off from the reaction system, and the solution was heated to 280°C at a heating rate of 1.0°C / min, and then decompressed at 280°C. After reacting at 280°C for 20 minutes, the temperature was then raised to 300°C and reacted for 20 minutes, and finally the temperature was raised to 320°C and reacted for 20 minutes. After that, the product was taken out from the reaction vessel and cooled to room temperature. The cooled product was crushed with a pulverizer to obtain a powdered liquid crystal polyester (A-9) of Synthesis Example 9. 8 g of the powdered liquid crystal polyester (A-9) was added to 92 g of N-methyl-2-pyrrolidone and heated to 140° C. to completely dissolve it, thereby obtaining a brown transparent solution.
[0156] Synthesis Example 10 to Synthesis Example 12
[0157] The synthesis methods of the liquid crystal polyesters of Synthesis Examples 10 to 12 are the same as those of Synthesis Example 9. The difference is that the amounts of each monomer and acetic anhydride used are changed. The formulas are shown in Tables 1 and 2.
[0158] Synthesis example 13
[0159] After nitrogen was introduced into a reaction vessel equipped with a nitrogen inlet, a stirrer, a heater, a condenser and a thermometer, 69.1 g (0.5 mol) of a2, 1035.0 g (5.5 mol) of a3, 432.4 g (2.0 mol) of b3 and 1123 g (11.0 mol) of acetic anhydride were added. Then, the above components were slowly stirred under a nitrogen stream to raise the temperature of the solution to 150°C, and a total of 218.3 g (2.0 mol) of c1-1 was added three times (each time with an interval of 1 hour) at this temperature, and then the reaction was maintained at the above temperature for 1 hour. Then, the by-product acetic acid and unreacted acetic anhydride were distilled off from the reaction system, and the solution was heated to 310°C at a heating rate of 1.0°C / min, and then decompression treatment was performed at a temperature of 310°C. After heating at a temperature of 310°C for 30 minutes, the product was taken out of the reaction vessel and cooled to room temperature. The cooled product was crushed with a pulverizer to obtain a powdered prepolymer. The flow temperature of the above prepolymer is 181°C. After that, the above prepolymer was heated from room temperature to 250°C under a nitrogen flow within 6 hours, and heated at 250°C for 10 hours to perform solid phase polymerization. Then, the product was cooled to room temperature and crushed, and then the above product was heated from room temperature to 255°C under a nitrogen flow within 6 hours, and then solid phase polymerization was performed again for 3 hours. After solid phase polymerization, the product was taken out of the reaction vessel and cooled to room temperature. After the cooled product was crushed with a pulverizer, a powdered liquid crystal polyester (A-13) of Synthesis Example 13 was obtained, and its flow temperature was 310°C. 8g of the powdered liquid crystal polyester (A-13) was added to 92g of N-methyl-2-pyrrolidone and heated to 140°C to completely dissolve it to obtain a brown transparent solution.
[0160] Synthesis Example 14
[0161] After nitrogen was introduced into a reaction vessel equipped with a nitrogen inlet, a stirrer, a heater, a condenser and a thermometer, 1317.3 g (7.0 mol) of a3, 387.3 g (1.5 mol) of b4, 163.7 g (1.5 mol) of c1-2 and 1123 g (11.0 mol) of acetic anhydride were added. Then, the above components were slowly stirred under a nitrogen stream to heat the solution to 140°C, react at this temperature for 1 hour, then heated to 150°C and reacted for 1 hour, and finally heated to 160°C and reacted for 1 hour. Then, the by-product acetic acid and unreacted acetic anhydride were distilled off from the reaction system, and the solution was heated to 290°C at a heating rate of 1.0°C / min, and then decompressed at 290°C. After heating at 300°C for 30 minutes, the product was taken out of the reaction vessel and cooled to room temperature. The cooled product was crushed with a pulverizer to obtain a powdered prepolymer. The flow temperature of the above-mentioned prepolymer is 181°C. Afterwards, the above-mentioned prepolymer is heated from room temperature to 250°C within 6 hours under a nitrogen flow, and heated at a temperature of 250°C for 10 hours to carry out solid phase polymerization. Then, the product is cooled to room temperature and crushed, and then the above-mentioned product is heated from room temperature to 255°C within 6 hours under a nitrogen flow, and solid phase polymerization is carried out again for 3 hours. After solid phase polymerization, the product is taken out from the reaction vessel and cooled to room temperature. After the cooled product is crushed with a pulverizer, a powdered liquid crystal polyester (A-14) of Synthesis Example 14 can be obtained, and its flow temperature is 310°C. 8g of the powdered liquid crystal polyester (A-14) is added to 92g of N-methyl-2-pyrrolidone and heated to 140°C to completely dissolve it to obtain a brown transparent solution.
[0162] Comparative Synthesis Example 1
[0163] In a reaction vessel equipped with a nitrogen inlet, a stirrer, a heater, a condenser and a thermometer, nitrogen was introduced, and then 138.1 g (1.0 mol) of a1, 747.6 g (4.5 mol) of b1, 163.7 g (1.5 mol) of c1-1, 453.5 g (3.0 mol) of c2-1 and 816.7 g (8.0 mol) of acetic anhydride were added. Then, the above components were slowly stirred under a nitrogen stream to heat the solution to 150°C, and reacted at this temperature for 3 hours. Then, the by-product acetic acid and unreacted acetic anhydride were distilled off from the reaction system, and the solution was heated to 300°C at a heating rate of 1.0°C / min, and then decompressed at 300°C. After reacting at 300°C for 1 hour, the product was taken out of the reaction vessel and cooled to room temperature. The cooled product was crushed with a pulverizer to obtain a powdered liquid crystal polyester (A'-1) of Comparative Synthesis Example 1. 8 g of the powdery liquid crystal polyester (A'-1) was added to 92 g of N-methyl-2-pyrrolidone and heated to 140° C. to completely dissolve the mixture, thereby obtaining a brown transparent solution.
[0164] Comparative Synthesis Example 2 to Comparative Synthesis Example 3
[0165] The synthesis methods of the liquid crystal polyesters of Comparative Synthesis Examples 2 to 3 are the same as that of Comparative Synthesis Example 1. The difference is that the amount of each monomer and acetic anhydride used is changed. The formulas are shown in Tables 1 and 2.
[0166] Comparative Synthesis Example 4
[0167] In a reaction vessel equipped with a nitrogen inlet, a stirrer, a heater, a calcium chloride filling tube, a condenser and a thermometer, after introducing nitrogen, 835.88g of N-methyl-2-pyrrolidone was added. Then, 78.55g of bis(4-aminophenyl)ether was added while slowly stirring under a nitrogen flow to completely dissolve it. After that, 85.57g of pyromellitic dianhydride was added dropwise within 5 hours while slowly stirring. Then, the reaction was carried out at 80°C for 12 hours. Finally, after the solution was cooled to room temperature, the polyimide precursor (A'-4) of Comparative Synthesis Example 4 was obtained.
[0168] In addition, the compounds corresponding to the abbreviations in Tables 1 and 2 are as follows.
[0169] Abbreviation Chinese name a1 Parabens a2 m-Hydroxybenzoic acid a3 6-Hydroxy-2-naphthoic acid b1 Terephthalic acid b2 Isophthalic acid b3 2,6-Naphthalenedicarboxylic acid b4 Diphenyl ether-4,4'-dicarboxylic acid b5 Benzophenone-4,4'-dicarboxylic acid c1-1 3-Aminophenol c1-2 4-Aminophenol c1-3 4-Amino-4'-hydroxybiphenyl c2-1 3-Hydroxyacetanilide c2-2 4-Hydroxyacetanilide c3-1 p-phenylenediamine c3-2 Biphenyl-4,4'-diamine
[0170] [Table 1]
[0171]
[0172] [Table 2]
[0173]
[0174] [Examples of Insulated Wires]
[0175] Example 1
[0176] The solution of the liquid crystal polyester (A-1) of Synthesis Example 1 was stirred and degassed to obtain a liquid composition. Then, the liquid composition was directly applied to the outer peripheral side of a copper conductor having a diameter of 1.0 mm through a mold, and the copper conductor was heated at a certain linear speed through a cylindrical baking furnace to form an insulating layer on the outer peripheral side of the copper conductor. In the baking furnace, the copper conductor was heated for 15 seconds in an environment of 300° C. or above. The above steps were repeated to form an insulating layer with a thickness of 30 μm on the outer peripheral side of the copper conductor.
[0177] Examples 2 to 14 and Comparative Examples 1 to 4
[0178] Examples 2 to 12 and Comparative Examples 1 to 4 use the same manufacturing method as the insulated wire of Example 1, except that the type of liquid crystal polyester and the film thickness of the insulating layer are changed. The evaluation results are shown in Table 3.
[0179] [Table 3]
[0180]
[0181] [Evaluation method]
[0182] Oxygen permeability
[0183] The oxygen permeability of each example and comparative example was measured under a 23° C. environment by a method in accordance with Japanese Industrial Standards (JIS) K-7126.
[0184] Partial discharge inception voltage
[0185] Two insulated wires obtained in each embodiment and comparative example were twisted to make a spiral test piece. A sinusoidal 50Hz AC voltage was applied between the conductors, and the voltage (effective value) was measured when the discharge amount was 10pC while continuously increasing the voltage, and the voltage at this time was set as the partial discharge inception voltage. The measurement temperature was set to room temperature (20°C). The partial discharge inception voltage was measured using a partial discharge tester (KPD2050 manufactured by Kikuchi Electric Chemical Industry Co., Ltd.).
[0186] Voltage application life
[0187] Two insulated wires obtained from each embodiment and comparative example are twisted together to form a spiral test piece. Next, a voltage of 110% of the above-mentioned partial discharge starting voltage is applied between each conductor. Specifically, if the partial discharge starting voltage is 600V, the applied voltage is 660V. The time until the insulation is broken after the above-mentioned voltage value is applied in an environment of 20°C is measured. The voltage application life evaluation criteria are as follows:
[0188] ◎: Voltage application time ≥ 5000 minutes
[0189] ○: 5000 minutes > voltage application time ≥ 4000 minutes
[0190] △: 4000 minutes > voltage application time ≥ 3000 minutes
[0191] ╳: Voltage application time <3000 minutes
[0192] [Evaluation results]
[0193] From Table 3, we know that the oxygen permeability is 1×10 -15 mol / m 2 .Pa.s or less, compared with the insulated wires (Examples 1 to 14) having an oxygen permeability of more than 1×10 -15 mol / m 2 The insulated wires of Comparative Examples 1 to 4 with an insulating layer having a thickness of .Pa.s were poor in the voltage application life evaluation.
[0194] In addition, when the monomers constituting the structural units derived from (C") in the insulating layer include aromatic hydroxylamine and aromatic hydroxyamide (Examples 1, 2, 5, 6, 9, and 10), the voltage application life of the obtained insulated wire can be further increased.
[0195] In summary, the insulated wire of the present invention has an oxygen permeability of 1×10 -15 mol / m 2 .Pa.s or less, so the insulated wire has a long voltage application life and excellent flexibility.
[0196] Furthermore, when the monomers constituting the structural unit derived from (C") in the insulating layer include aromatic hydroxylamine and aromatic hydroxyamide, the voltage application life of the obtained insulated wire can be further increased.
[0197] Although the present invention has been disclosed as above by way of embodiments, it is not intended to limit the present invention. Any person having ordinary knowledge in the technical field may make some changes and modifications without departing from the spirit and scope of the present invention. Therefore, the protection scope of the present invention shall be based on that defined by the claims.
Claims
1. An insulated wire, comprising: conductor; as well as an insulating layer, laminated on the outer peripheral side of the conductor, The insulating layer includes liquid crystal polyester, The oxygen permeability of the insulating layer is 1×10 -15 mol / m 2 .Pa.s below.
2. The insulated wire according to claim 1, wherein The liquid crystal polyester comprises structural units derived from the following (A), (B), and (C), (A) Aromatic hydroxycarboxylic acid (B) Aromatic dicarboxylic acid (C) at least one compound selected from the group consisting of aromatic diols, aromatic diamines, and aromatic amines having a phenolic hydroxyl group.
3. The insulated wire according to claim 2, wherein The liquid crystal polyester comprises structural units derived from the following (A'), (B'), and (C'), (A')-O-Ar 1 -WHAT- (B')-CO-Ar 2 -WHAT- (C’)-X-Ar 3 -Y- in, Ar 1 represents phenylene, naphthylene or biphenylene, Ar 2 represents a phenylene group, a naphthylene group, a biphenylene group, or a group formed by condensation of multiple aromatic groups, Ar 3 represents a phenylene group or a group formed by condensation of a plurality of aromatic groups, and X and Y represent -O- or -NH-, respectively.
4. The insulated wire according to claim 3, wherein The liquid crystal polyester comprises structural units derived from the following (A'), (B'), and (C"), (A')-O-Ar 1 -WHAT- (B')-CO-Ar 2 -WHAT- (C”)–NH–Ar 3 -THE- in, Ar 1 represents phenylene, naphthylene or biphenylene, Ar 2 represents a phenylene group, a naphthylene group, a biphenylene group, or a group formed by condensation of multiple aromatic groups, Ar 3 represents a phenylene group or a group formed by condensation of a plurality of aromatic groups, and Y represents -O- or -NH-.
5. The insulated wire according to claim 4, wherein The monomers constituting the (C") include aromatic hydroxylamines and aromatic hydroxyamides.
6. The insulated wire according to claim 5, wherein Based on 100 mol% of the total amount of monomers constituting the (C"), the amount of the aromatic hydroxylamine used is 30 to 90 mol%, and the amount of the aromatic hydroxyamide used is 10 to 70 mol%.
7. The insulated wire according to claim 1, wherein The oxygen permeability of the insulating layer is 8×10 -16 mol / m 2 .Pa.s below.
8. The insulated wire according to claim 1, wherein The oxygen permeability of the insulating layer is 5×10 -16 mol / m 2 .Pa.s below.
9. The insulated wire according to claim 1, wherein The thickness of the insulating layer is not less than 2 μm and not more than 50 μm.
10. A method for manufacturing an insulated wire, comprising manufacturing the insulated wire according to any one of claims 1 to 9, the method comprising: A coating step of coating a liquid composition on the outer peripheral side of the conductor, wherein the liquid composition includes a liquid crystal polyester and an aprotic solvent; as well as The heating step is to heat the conductor coated with the liquid composition.
11. A coil comprising the insulated wire according to any one of claims 1 to 9.
12. An electronic machine comprising the coil according to claim 11.
Citation Information
Patent Citations
Electric wire coating material and electric wire
JP2008159359A
Insulated wire, production method thereof, coil and motor
JP2014225433A